Α-Asarone Alleviated Chronic Constriction Injury–Induced Neuropathic Pain Through Inhibition of Spinal Endoplasmic Reticulum Stress in an Liver X Receptor–Dependent Manner. (September 2018) - Gui, Yulong; Li, Aiyuan; Zhang, Jie; Li, Guan; Ruan, Xia; Guo, Qulian; Zou, Wangyuan
Abstract : BACKGROUND: Neuropathic pain is an intractable and complex disease. Recent studies have shown a close relationship between endoplasmic reticulum (ER) stress and neuropathic pain. Here, we investigated the effect of α-asarone, an ER stress inhibitor, on chronic constriction injury (CCI)–induced neuropathic pain. METHODS: Two parts were included in this study. In part 1, rats were assigned to 7 groups: the sham group, the sham + α-asarone 20 mg/kg group, the CCI group, the CCI + vehicle group, the CCI + α-asarone 5 mg/kg group, the CCI + α-asarone 10 mg/kg group, and the CCI + α-asarone 20 mg/kg group. After surgery, the rats were treated with α-asarone or normal saline daily. Pain thresholds were measured, and samples of the L3–6 spinal cord were taken for western blotting and immunofluorescence on day 7. In part 2, rats were intrathecally implanted with PE-10 tubes and divided into 4 groups: the CCI + α-asarone 20 mg/kg group, the CCI + α-asarone 20 mg/kg + vehicle group, the CCI + α-asarone 20 mg/kg + SR9243 group, and the CCI group. Five rats in each group were separated for behavioral tests 1 hour after intrathecal injection. The rest of them were killed for western blotting on day 7. RESULTS: In this study, CCI surgery significantly induced mechanical allodynia and thermal hyperalgesia. CCI surgery significantly induced activation of ER stress (PERK-eIF2α, IRE1α, CHOP, and XBP-1s) in rats. However, treatment with 20 mg/kg of α-asarone significantly alleviated CCI-induced activation of ER stress. Behavioral results showed that daily treatment with 20 mg/kg of α-asarone significantly alleviated CCI-induced nociceptive behaviors, on day 7 (mechanical allodynia, P = .016, 95% confidence interval, 0.645–5.811; thermal hyperalgesia, P = .012, 95% confidence interval, 0.860–6.507). Furthermore, α-asarone induced upregulated expression of liver X receptor β (LXRβ) and downstream proteins in the spinal cord. The LXR antagonist SR9243 completely inhibited the anti-ER stress and antinociceptive effects of α-asarone in rats. CONCLUSIONS: α-Asarone relieved CCI-induced neuropathic pain in an LXR-dependent manner. α-Asarone may be a potential agent for treatment of neuropathic pain.